Septicemia associated with omphalitis in a goat kid - Abdullah, Jesse Faez Firdaus; Abba, Yusuf; Tijjani, Abdulnasir; Mohammed, Konto; Muhammad, Abubakar Sadiq; Lim, Eric Teik Chung; Saharee, Abdul Aziz; Haron, Abdul Wahid (Pashupati Foundation India, 2015)
This case report describes a case of suspected omphalitis in a female two-week-old Katjang cross kid. The kid was weak and on lateral recumbency. It had hypothermia, bradycardia and shallow breathing with thumping sound at the end or expiration. The kid died and post-mortem examination revealed multiple hepatic abscesses, fibrin attachment between the liver and the diaphragm, cloudy yellow fluid in the peritoneal cavity and severe generalized congestion of the small intestine. The findings suggest the kid had died of a septic shock.